Ultrasound-guided bilateral pudendal nerve blocks of nulliparous women with epidural labour analgesia in the second stage of labour: a randomised, double-blind, controlled trial - Jialing Xu; Riyong Zhou; Weijue Su; Shi Wang; Yun Xia; Thomas Papadimos; Junzhao Zhao; Xuzhong Xu (BMJ Open)
Objective To explore whether an ultrasound-guided pudendal nerve block (PNB) could decrease anaesthetic use, thereby shortening the length of the second stage of labour in women undergoing epidural analgesia.Design Prospective, single-centre, randomised, double-blind, controlled trial.Setting An obstetric centre in a general hospital in China.Participants 72 nulliparous women were randomised, and 71 women completed the study.Intervention An ultrasound-guided bilateral PNB was administered to all study participants; the PNB group were given 0.25% ropivacaine 10 mL, while the control group were given 10 mL saline.Main outcome measure The primary outcome measure was the duration of the second stage of labour. Secondary outcomes included additional bolus administration, total hourly bupivacaine consumption, difference in thickness between the contracted and relaxed rectus abdominis muscle before (DRAM1) and 30 min after (DRAM2) PNB, urge to defecate, maternal cooperation, preservation of the lower limb motor function, tightness of the perineum, and Numeric Rating Scale (NRS) score for pain.Results The duration of the second stage of labour was shorter in the PNB group than in the control group (difference of 33.8 min (95% CI 15.6 to 52.0), p<0.001). Additional bolus administration and total hourly bupivacaine consumption were lower in the PNB group than in the control group (p<0.001). DRAM2 was greater (p<0.001), rate of parturient women with the urge to defecate was higher (p=0.014), maternal cooperation was superior (p=0.002), and lower limb motor function preservation was greater (p=0.004) in the PNB group relative to the control group. Tightness of the perineum was eliminated from the results due to the inconsistent application of the criteria by the nursing staff. There was no significant difference in NRS scores between the groups.Conclusions Nulliparous women with epidural analgesia who received an ultrasound-guided bilateral PNB may reduce their need for bupivacaine and consequently shorten the length of the second stage of labour, therein indicating that a bilateral PNB may serve as an additional effective adjunct method of labour analgesia.Trial registration number ChiCTR-IOR-16009121.